Microvascular reconstruction of facial defects in settings where resources are limited. Issue 1 (January 2016) - Rodgers, W.; Lloyd, T.; Mizen, K.; Fourie, L.; Nishikawa, H.; Rakhorst, H.; Schmidt, A.; Kuoraite, D.; Bulstrode, N.; Dunaway, D.
Abstract: The surgical treatment of defects caused by noma is challenging for the surgeon and the patient. Local flaps are preferred, but sometimes, because of the nature of the disease, there is not enough local tissue available. We describe our experience of free tissue transfer in Ethiopia. Between 2008 and 2014, 34 microsurgical procedures were done over 11 missions with the charity Facing Africa, predominantly for the treatment of defects caused by noma (n = 32). The mean duration of operation was 442 minutes (range 200 – 720). Six minor wound infections were treated conservatively and did not affect outcome, a return to theatre was required in 4 patients with wound infections and one with a haemorrhage; 2 flaps failed and 2 partially failed, one patient developed an oronasal fistula, and one had an infection at the donor site that required a repeat graft. In settings where resources are limited, free flaps can be used when local tissue is not available and they cause less morbidity than pedicled tissue transfer.